Sprouts: Safe Handling Practices for Consumers - Amy Simonne (EDIS)
This publication is FCS8739, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: November 2002.